Normative performance of healthy older individuals on the Modified Mini-Mental State (3MS) examination according to ethno-racial group, gender, age, and education level - Ryan, J.; Woods, R.; Britt, C.; Murray, A.; Shah, R.; Reid, Christopher; Kirpach, B.; Wolfe, R.; Nelson, M.; Lockery, J.; Orchard, S.; Trevaks, R.; et al. (Psychology Press, 2018)
Objective: To present normative performance data on the Modified Mini-Mental State (3MS) examination for healthy community-dwelling older individuals according to gender, age, education level, and ethno-racial group. Method: More than 19,000 generally healthy older men and women without a diagnosis of dementia were recruited from the general population in Australia and the U.S. for the ASPirin in Reducing Events in the Elderly (ASPREE) study. The 3MS exam was administered as part of the baseline screening and individuals scoring above 77 were eligible to participate. Results: The sample comprised 16,360 Australian whites, 1080 U.S. whites, 895 African-Americans and 316 Hispanic/Latinos. The median age of participants was 74 years (range 65–98), with an average of 12 years of education and 56% were female. Increasing age and fewer years of completed education were associated with lower scores on the 3MS. Women scored higher than men in most age and education categories. Differences across ethno-racial groups were found. With factor analysis, four factors were identified which accounted for 35% of the between-person variance in 3MS scores for white Australians. Conclusions: This large cohort of older individuals provides some of the most comprehensive 3MS normative data to be generated for whites (Australian and U.S.), Hispanic/Latinos and African-Americans, by age, gender, and educational attainment. These findings will serve as important reference standards for monitoring cognitive function in generally healthy older individuals, becoming increasingly important as this fraction of the population increases.